The Adverse Reactions of Erythropoietin in Methanol Toxicity: A Descriptive Study - Mohebpour, Vahidreza; Rahimi, Mitra; Shadnia, Shahin; Mostafazadeh, Babak; Talab Evini, Peyman Erfan (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: Nowadays, erythropoietin is employed as a substitute therapy for eye ailments, particularly optic nerve damage induced by methanol toxicity. Despite its benefits, erythropoietin can have negative effects on blood factors. These effects may include thrombosis, stroke, seizures, and changes in hematological function. This study examined the adverse effects of erythropoietin on individuals suffering from optic neuropathy caused by methanol. Methods: This study was a prospective descriptive study at Loghman Hakim Hospital, Tehran City, Iran, in 2022. The study involved individuals who suffered from methanol poisoning and were administered erythropoietin twice a day for three days, with a dosage of 10000 units each time. Patients were examined up to 6 weeks after discharge in terms of increased hemoglobin levels, seizures, central vascular thrombosis, and heart attack or stroke. The data was analyzed by SPSS software, version 18. Results: The study comprised of 37 patients. No patient reported seizures, heart and cerebral strokes, and deep vein thrombosis except polycythemia. After being discharged from the hospital, the mean hemoglobin levels increased by 2.01% six weeks later compared to the levels measured during admission. Moreover, there was a 2.4% rise in hemoglobin levels six weeks after discharge when compared to the levels measured two weeks after being discharged. Conclusion: Using erythropoietin to treat optic neuropathy can improve vision, but it also carries the risk of increasing hemoglobin levels, which must be monitored closely in treated patients.